Causative Factors Affecting Buddhist Tourism of Temples in Phra Nakhon Si Ayutthaya Province - Kanthawong , Noppadol; Karawek, Sirachaya (Journal for Developing the Social and Community, 2023)
This research aims to: (1) To study the importance of Buddhist tourism marketing strategies, Buddhist tourism marketing activities and Buddhist tourism components of temples in Ayutthaya province. (2)Analyze the causal relationship between tourism marketing strategies, tourism marketing activities that affect tourism components and lead to the promotion of Buddhist tourism values ​​of temples in Ayutthaya province. And (3) Create a marketing promotion model for Buddhist tourism of temples in Phra Nakhon Si Ayutthaya Province. This research is a combination of quantitative research and qualitative research. The quantitative research was done using a questionnaire data collection method of 405 Thai tourists who traveled to temples in Phra Nakhon Si Ayutthaya Province, 9 temples, totaling 405 people. Sampling with a quota random sampling method. The qualitative research used in-depth interviews with a semi-structured interview form from 28 key informants. The statistics used to analyze the data are percentage, mean, and standard deviation. Data analysis to test the research hypothesis was based on structural equation analysis by AMOS program. The results showed that: (1) Tourists pay high attention to Buddhist tourism marketing strategies, Buddhist tourism marketing activities, and Buddhist tourism components of temples in Ayutthaya province at a high level. (2) The results of the causal model analysis revealed that the model according to the research conceptual framework was harmonious with the empirical data with the following conformance index values: c2=137.09, df=113, c2 / df = 1.21, p-value = 0.06, ค่า GFI = 0.98, AGFI = 0.95, CFI = 1.00, NFI = 1.00, and TLI = 1.00, SRMR = 0.020, RMSEA = 0.020. The causal variable that had the most direct influence on the promotion of Buddhist tourism values ​​was tourism activities, followed by tourism marketing strategies, and Buddhist tourism components respectively. The three variables could explain the variance in the value promotion of Buddhist tourism (R2) as 0.80(80.0%). (3) The results of this research present a model of marketing promotion of Buddhist tourism of temples in Phra Nakhon Si Ayutthaya Province.